Analisis Kualitas Udara (Parameter Jamur) pada Ruang Tunggu Puskesmas Perawatan Kassi-Kassi dan Non- Perawatan Tamangapa di Kota Makassar - Hartati, Hartati; -, Misnarliah (Jurnal Sehat Mandiri, 2023)
Room air quality that does not meet the requirements is proportional to the number of germs in the room. Community Health Center are not only visited by sick people but also healthy people, so that puskesmas have the potential to become places for disease transmission. Mold is one of the microorganisms that can determine indoor air quality. The aim of this research is to determine air quality through the concentration of air mold, and the factors that influence the concentration of air mold in the waiting rooms of the Treatment and Non-Maintenance Health Centers. Waiting room air samples were taken at the Kassi-Kassi and Tamangapa non-care health centers using passive methods. Air samples were grown on SDA media. The results of this research were that there were 7 types of fungal isolates isolated from the Kassi-Kassi and Non-Care Health Centers in Tamangapa Makassar, namely: Aspergillus niger.,Aspergillus flavus.,Aspergillus nidulans.,Fusarium sp.,Rhizopus sp.,Saccharomyces sp.,and trichophyton rubrum. There was no significant difference in fungal concentrations in the waiting rooms of the Kassi-Kassi and Non-Care Tamangapa Makassar Health Centers. The average value of air mold concentration in the waiting room of the Kassi-Kassi Care Health Center has an average of 6.44 CFU/m3, while the Tamangapa Non-Care Health Center has an average of 6.44 CFU/m3, still below the maximum standard determined by WHO in 2009 regarding Mold and Dampness Indoor Air, namely less than 500 CFU/m3.